Policy Feedback and Civic Engagement: Evidence from the Finnish Basic Income Experiment - Salomo Hirvonen; Jerome Schafer; Janne Tukiainen (Aboa Centre for Economics (ACE), 2023)
In many democracies, unemployed and low-income citizens are less willing to vote. Can unconditional cash transfers weaken the link between income and turnout? We study a unique experiment in Finland, which randomly assigned a sizable group of unemployed to basic income for two years (2017-19). Leveraging individual-level registry and survey data, we show that replacing conditional unemployment benefits with unconditional basic income has large positive effects on actual voter turnout and subjective levels of political efficacy. On average, the intervention increases turnout in municipal elections by about 3 p.p., an effect that is magnified among marginal voters(+ 6-8 p.p.) and persists in national elections after the end of the experiment. Our analysis suggests that the turnout effects are driven by unconditionality increasing social capital - rather than income itself. We discuss implications for theories of voter turnout and policy feedback, and the design of basic income policies.
Keywords: C93; D72; 330; Basic income; Field experiment; Turnout